Perinatal mental health in Singapore—prevalence, knowledge, attitudes, and practices - Quah, Phaik Ling; Poo, Zi Xi; Chen, Helen Yu; Chua, Tze-Ern; Tan, Lay Kok; Tan, Kok Hian (Frontiers in Medicine, 2025)
IntroductionThere is limited data on perinatal depression and anxiety rates, as well as on knowledge, attitudes, and practices related to perinatal mental health (PMH), particularly in an urban Southeast Asian population.MethodsFrom September to December 2022, 446 antenatal and 150 postnatal participants completed a 38-item survey assessing depressive and anxiety symptoms, along with knowledge, attitudes, and practices regarding PMH. Probable depression was defined as an Edinburgh Postnatal Depression Scale (EPDS) score of ≥15 during pregnancy or ≥13 postnatal. Probable anxiety was defined using the EPDS anxiety subscale (EPDS-3A), which comprises items 3, 4, and 5, with a score of ≥5 indicating probable anxiety.ResultsThe rates of probable depression were 11.9% antenatally and 23.7% postnatally, while anxiety rates were 48.4% and 56.7%, respectively. Only 63.8% of participants could identify symptoms of mental health disorders, and just 24.1% had received assessment or education from healthcare professionals. Although most women (57.0%) would seek support from their spouse or partner, only 15.5% indicated willingness to consult healthcare professionals. Most participants supported the need for mental health education (89.5%), screening (87.4%), and tailored guidelines (94.5%) for perinatal women.ConclusionHigh rates of probable depression and anxiety, coupled with low mental health literacy, highlight the urgent need for comprehensive PMH education and guidelines in Singapore.